Analysis of the Influence of Audit Opinion on Regional Financial Management in Medan, North Sumatra - Ramadhani, Dea; Siregar, Faijah Maya Sari; Ginting, Puji Aloina Br; Khaira, Syakila Niswatul; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
Regional financial management is the key to good governance, especially in regional autonomy that gives great authority to local governments, with high demands for accountability and transparency. The audit opinion of the Supreme Audit Agency (BPK) assesses the fairness of financial reports based on accounting principles. This study examines the influence of audit opinions on the financial management of Medan City, which for four consecutive years has received an Unqualified Opinion (WTP). Although it shows the quality of reporting, cases such as the Pocong Lamp and the ceramic road indicate budget inefficiency. With a Regional Financial Independence Ratio (RKD) of 41.38%, Medan City is still highly dependent on central transfers, reflecting weak fiscal autonomy. The existence of a problematic budget of 1.32% of PAD emphasizes the need for improvement. This study is expected to support the improvement of accountable, transparent, and community welfare-oriented financial management.